Understanding Police Performance: The Mediating Effect of Work Motivation on the Relationship between Work Environment, Compensation, and Performance - Syahruddin Syahruddin; Jamaluddin B. Ilyas; Bahtiar Maddatuang (Vifada Management and Social Sciences, 2024)
Police institutions play a critical role in maintaining public security, social order, and law enforcement effectiveness. The performance of police officers is therefore a key indicator of institutional success in managing criminal cases and ensuring public safety. This study aims to examine the effects of work environment and compensation on police performance, with work motivation serving as a mediating variable. A quantitative research design grounded in the positivist paradigm was employed. Data were collected through a structured questionnaire distributed to 94 police officers of a regional police department in South Sulawesi, Indonesia. The data were analyzed using path analysis to assess both direct and indirect relationships among variables. The findings reveal that the work environment has a significant positive effect on work motivation, while compensation also significantly influences motivation. Furthermore, both work environment and compensation have significant direct effects on police performance. Work motivation is found to significantly enhance performance and to mediate the relationships between work environment, compensation, and police performance. These results highlight the importance of creating a supportive work environment and implementing fair compensation systems to strengthen motivation and improve performance in law enforcement organizations. The study contributes to the literature on public sector performance by emphasizing the strategic role of motivational mechanisms in enhancing police effectiveness.